Pokrajina v luči retoričnih figur v besedilih o slovenski Istri - Urbanc, Mimi (Primerjalna književnost, 2013)
The article discusses the geographical notions of the landscape in Slovenian Istria produced by rhetorical figures. It is based on the premise that figurative language is a mechanism that contributes to the cognitive and representational processes that take place in the literary and non-literary contexts, and is thus suitable for studying the perception and formation of one's relationship to the landscape.
Keywords: geografija; geography; Slovene literature; slovenska književnost; Subdivisions of the Kingdom of Yugoslavia; pokrajina; literarna besedila; retorične figure; Istra (Slovenija)